OPERASI MOTOR LISTRIK DENGAN SISTEM KENDALI STAR DELTA MENGGUNAKAN PLC ZELIO SR3B101FU - Ari Kurniawan; Yulisman Yulisman (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
Electric motors are electrical appliances widely used in industrial and university scopes, as well as FT-UMSB Electrical Engineering laboratory. In the study of electric motors, it is important for us to understand the comparison between the start current and the time. The analysis was done in three ways, namely the relationship of DOL star, the relationship of DOL delta and star-delta starting. The main control system in the control circuit that will test the current ratio is the Zelio SR3B101FU PLC. The test is done by connecting an electric motor with the PLC control circuit Zelio SR3B101FU to extract large data current and time required to achieve normal motor operation.